Media, Pulpit, and Populist Persuasion: Evidence from Father Coughlin - Wang, Tianyi (American Economic Review, 2021)
I study the political impact of the first populist radio personality in American history. Father Charles Coughlin blended populist demagoguery, anti-Semitism, and fascist sympathies to create a hugely popular radio program that attracted 30 million weekly listeners in the 1930s. I find that exposure to Father Coughlin’s anti-Roosevelt broadcast reduced Franklin D. Roosevelt’s vote share in the 1936 presidential election. Coughlin’s effects were larger among Catholics and persisted after Coughlin left the air. Moreover, places more exposed to Coughlin’s broadcast were more likely to form a local branch of the pro-Nazi German-American Bund and sold fewer war bonds during World War II. (JEL D72, L82, N32, N42, Z12)